Unbroken : a World War II story of survival, resilience, and redemption - Hillenbrand, Laura (New York Random House, 2014)
Unbroken, the inspiring true story of a man who lived through a series of catastrophes almost too incredible to be believed. In evocative, immediate descriptions, Hillenbrand unfurls the story of Louie Zamperini--a juvenile delinquent-turned-Olympic runner-turned-Army hero. During a routine search mission over the Pacific, Louie?s plane crashed into the ocean, and what happened to him over the next three years of his life is a story that will keep you glued to the pages, eagerly awaiting the next turn in the story and fearing it at the same time.
Keywords: Military operations, Aerial--American; Prisoners of war; Zamperini, Louis, 1917-2014; Pacific Area; Japan; United States